Prevenga la Osteoporosis: Atrape al Ladrón Silencioso - Linda B. Bobroff (EDIS)
Revised! FCS8145-Span, an 11-page fact sheet by Linda Bobroff, is the Spanish version of "Prevent Osteoporosis: Stop the Silent Thief." It provides statistics and facts about osteoporosis and information about how to stop this "silent thief" of bone density. Includes calcium-rich recipes. Published by the UF Department of Family, Youth and Community Sciences, April 2007.